Świadek przekonań – podmiot sumienia : Paul Ricoeur i filozofia świadectwa - Grzywacz, Robert (2020)
In the book which the reader finds in their hands, I attempt to justify the hypothesis that the hermeneutical philosophy of Paul Ricoeur pro-vides a solid framework and conceptualisation for a coherent approach to the coexistence of different religious convictions in the situation of worldview pluralism. The chosen hermeneutics develops its own as-sumptions which are gradually clarified in the course of the presenta-tion of the aforementioned framework and concepts. At the same time, the coherence of all the arguments turns out to be a test of the rational-ity and universality of these hermeneutical foundations. Additionally, I try to demonstrate the productivity of reading the works of the French thinker, not only in chronological order but also retrospectively. Thus, some phenomenological analyses serve to make the subsequent herme-neutical-ontological attainments more concrete. This is precisely what is intended by the description of the functioning of attention, inasmuch as it is related to how the human conscience works
Keywords: discourse; convictions; testimony; witness; conscience; biblical faith